2006
DOI: 10.1196/annals.1375.038
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of CTLA‐4 Gene CT60 Polymorphism May Not Be Affected by Vitamin D Receptor Gene Bsm I Polymorphism or HLA DR9 in Autoimmune‐Related Type 1 Diabetes in the Japanese

Abstract: One of the CTLA-4 SNPs, +6230G>A (CT60), has recently been reported to be related to susceptibility to type 1 diabetes and autoimmune thyroid disease. We have previously reported an association between acute-onset type 1 diabetes in Japanese and the Vitamin D receptor (VDR) gene Bsm I large B polymorphism, which is related to the Th1-type response. Moreover, we found a significant correlation between autoimmune-related type 1 diabetes with HLA DR9 and detection of GAD-reactive Th1 (T helper 1)-type cells. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Some investigators presumed that the VDR polymorphisms influence bone resorption and immune function (Mathieu et al 2001, Froicu & Cantorna 2007, van Etten et al 2007, Garcia et al 2007). Several studies on the association between VDR polymorphisms and autoimmune diseases have been reported (Fan et al 2005, Kanazawa et al 2006, Birlea et al 2006, Maalej et al 2008). In the current study, we found that chronic periodontitis cases had a significantly lower frequency of bb genotype of Bsm I, higher frequency of AA genotype of Apa I and TT genotype of Taq I in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators presumed that the VDR polymorphisms influence bone resorption and immune function (Mathieu et al 2001, Froicu & Cantorna 2007, van Etten et al 2007, Garcia et al 2007). Several studies on the association between VDR polymorphisms and autoimmune diseases have been reported (Fan et al 2005, Kanazawa et al 2006, Birlea et al 2006, Maalej et al 2008). In the current study, we found that chronic periodontitis cases had a significantly lower frequency of bb genotype of Bsm I, higher frequency of AA genotype of Apa I and TT genotype of Taq I in Asians.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are 65 publications [19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83] on the association of VDR gene SNPs in T1D: these include case-control datasets [20,22,23,25,26,27,28,…”
Section: Vitamin D Pathwaysmentioning
confidence: 99%
“…A total of 39 publications support an association between VDR SNPs rs7975232 ( ApaI ), rs1544410 ( BsmI ), rs731236 ( TaqI ) and rs10735810 ( FokI ) alone or in combination with each other, (rs757343 Tru9I , rs1540339 and rs4760648) and T1D [19,21,22,23,24,26,27,28,29,30,34,35,36,37,38,40,41,42,43,44,46,48,49,50,52,53,55,56,59,60,61,62,63,65,68,69,70,71,73] (Table 2) in comparison with 16 studies that refute it [20,25,31,32,39,45,47,51,54,57,58,64,66,67,72,74]. …”
Section: Vitamin D Pathwaysmentioning
confidence: 99%
“…A total of 7 references published on the association between the rs3087243 polymorphism and T1D were identified according to our inclusion criteria, involving 7085 cases and 9963 controls (Zhernakova et al, 2005;Baniasadi et al, 2006;Ikegami et al 2006;Kanazawa et al, 2006;Howson et al 2007;Douroudis et al, 2009;Benmansour el al., 2010). The main characteristics of these studies are described in Table 1.…”
Section: Identification Of Eligible Studiesmentioning
confidence: 99%
“…All these genes are in close linkage (Bartsocas et al 2006). Many molecular epidemiologic studies have evaluated the potential role of rs3087243 (Ueda et al, 2003;Kawoura and Loannidis, 2005;Zhernakova et al, 2005;Ikegami et al, 2006;Kanazawa et al, 2006;Caputo et al, 2007;Howson et al, 2007) in susceptibility to T1D. Given the amount of accumulated data, we believe that it is important to perform a quantitative synthesis of the evidence.…”
Section: Introductionmentioning
confidence: 99%